2013
DOI: 10.1590/s1984-82502013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical characters of the medicinal leaf and stem of Gymnanthemum amygdalinum (Delile) Sch.Bip. ex Walp. (Asteraceae)

Abstract: Gymnanthemum amygdalinum (Delile) Sch.Bip. ex Walp. (Asteraceae), better known by its former name Vernonia amygdalina Delile, is a small shrub used in folk medicine as an antipyretic, laxative, antimalarial and anthelmintic. Studies have demonstrated that different vegetal extracts possess antioxidant, antimicrobial and antiparasitic activities. Among the bioactive metabolites, there are sesquiterpene lactones, saponins, polyphenols and flavonoids. This study investigated the leaf and stem microscopic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The epidermal tissue of Plumeria rubra and Rauwolfia serpentine has been reported to have a thick cuticle [40]. Similar results are reported by Poornima et al [33], Duarte and Larrosa [20], and Albert et al [45], who reported that the epidermis consisted of a single layer and was covered with a thick cuticle in some members of Apocynaceae.…”
Section: Epidermal Layerssupporting
confidence: 71%
See 4 more Smart Citations
“…The epidermal tissue of Plumeria rubra and Rauwolfia serpentine has been reported to have a thick cuticle [40]. Similar results are reported by Poornima et al [33], Duarte and Larrosa [20], and Albert et al [45], who reported that the epidermis consisted of a single layer and was covered with a thick cuticle in some members of Apocynaceae.…”
Section: Epidermal Layerssupporting
confidence: 71%
“…The trichomes of Carissa macrocarpa has been reported as non-glandular [13]. Additionally, Mandevilla coccinea trichomes are non-glandular, unicellular, and with acute or round apex [20]. Akyalçın et al [44] reported that the hairs of Amsonia orientalis are unicellular.…”
Section: Trichomesmentioning
confidence: 99%
See 3 more Smart Citations